Interaksi Pembelajaran Pendidikan Agama Islam pada Peserta Didik Berkebutuhan Khusus di Sekolah Dasar Negeri 30 Palembang - Yulianti Yulianti; Dian Erlina (Bahasa Indonesia, Bahasa English, 2019)
Learning interaction is a reciprocal relationship between students and educators, between students, students with learning resources, and students with the learning environment in teaching and learning activities to achieve goals. In learning interactions also occur social interaction and communication. The purpose of this study, first, is to analyze the interaction of learning of autistic students in Islamic Religious Education subjects at Sekolah Dasar Negeri 30 Palembang, including; learning interactions between Islamic Religious Education teachers and autistic students, and learning interactions between students in general and autistic students. secondly, to analyze the constraints of the learning interactions of autistic students in Islamic Religious Education subjects at Sekolah Dasar Negeri 30 Palembang. The approach used in this research is a qualitative approach, and the type of research used in this study is a case study, data collection techniques, namely observation, interviews, and documentation. Data analysis techniques in this study used the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions.